La importancia de la educación financiera y análisis de una herramienta para incentivar el ahorro en los jóvenes de la ciudad de Duitama - Rachez Gomez, Lucy Amanda (Universidad Antonio Nariño, 2024)
The development of this work focuses on examining the saving behavior among young people and how financial education influences 4 their financial decisions at an early age, through an evaluative analysis it will be identified at what level financial education young people are and if they have access to financial services or different services.